Peningkatan Kemampuan Bahasa Anak Melalui Metode Bercerita Dengan Media Diorama - Anggraeni, Denok Dwi (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2021)
The purpose of this research was to determine the process of implementation of learning activities using storytelling methods with dioramas media in improving the language skills of children in group B and to know the extent of the results of improving children's language skills through storytelling methods with dioramas in group B. The method used in this research is an action research which refers to the model of a Classroom Action Research Kemmis and Mc. Taggart consist of four phase: planning, action, observation and reflection. This research consist of two cycles, each cycle consist of 6 times in actions. Analysis of the data used quantitative and qualitative approaches. Analysis of quantitative data used descriptive statistics that compare the results obtained from the first cycle and the second cycle. While the analysis of qualitative data used analyzing data from the field notes and interviews during the research by steps of data reduction, data display and data verification. The results showed an improvement in language skills through storytelling methods with dioramas, as evidenced by the average pre-action language proficiency score of children by 39%. Then increased in cycle I by 20% to 59%. Furthermore, from cycle I to cycle II children's language skills increased by 30% from 59% to 89%. So that the total improvement of children's language skills ranging from pre-action, cycle I to cycle II 39% which is 59% to 89%.